Comparative Evaluation of Postoperative Pain Scores and Opioid Consumption in Septorhinoplasty After Administration of Single-Dose Preemptive Paracetamol and Ibuprofen: A Randomized Controlled Trial - Alshehri, Ali Abdullah (International Archives of Otorhinolaryngology, 2023)
Introduction Septorhinoplasty operates on the nose's bone and cartilage and is ensued by severe postoperative pain.Objective The objective of this study is to evaluate the effects of preoperative administration of intravenous (IV) paracetamol and ibuprofen on postoperative pain scores in patients undergoing septorhinoplasty.Methods A total of 150 patients undergoing septorhinoplasty were randomly assigned into 3 groups with 50 patients in each group. The control group (group A) was administered 100 ml saline solution; the paracetamol group (group B) was administered 1,000 mg of IV paracetamol in 100 ml of saline solution; and the ibuprofen group (group C) was administered 800 mg of IV ibuprofen in 100 ml of saline solution before surgery. Opioid analgesics were employed to achieve postoperative analgesia. Postoperative pain was evaluated using the visual analogue scale (VAS). Postoperative opioid consumption and adverse effects were also recorded for each patient.Results In comparison with group A, the score in the VAS of groups B and C was statistically lower in all the time intervals (p < 0.05). In the 1st and 6th hours postoperatively, group C's score in the VAS in was lower than that of group B (p < 0.05). In the control group, total opioid consumption was highest in all time intervals (p < 0.05). In group C, total opioid consumption was significantly lower than in group B in the 0 to 6 and 6 to 12 hours intervals. (p < 0.05).Conclusion The single-dose preemptive administration of ibuprofen has a more profound postoperative analgesic effect than paracetamol in the first 6 hours after septorhinoplasty. After the first 6 hours postsurgery, there is no difference between ibuprofen and paracetamol in terms of analgesic effect.
Keywords: nasal septum/surgery; rhinoplasty/methods; analgesics; visual analog scale; pain; postoperative/diagnosis; treatment outcome